2018
DOI: 10.31067/0.2018.64
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite Öğrencilerinde Sağlıklı Yaşam ve Depresyon Puan Düzeyleri ile İlgili Faktörlerin Belirlenmesi

Abstract: Bu çalışmanın amacı üniversite öğrencilerinin sağlıklı yaşam alışkanlıkları ve bunlarla ilişkili etmenleri saptamaktır. Yöntem: Veriler 303 öğrenciye "sosyo demografik özellikler anketi", beslenme alışkanlıkları formu", "Sağlıklı Yaşam Biçimi Davranışları Ölçeği (SYBDÖ) ve "Beck Depresyon Ölçeği (BDÖ)" uygulanarak toplandı. Bulgular: Örneklemin yaş ortalaması 20.2, BDÖ puan ortalaması 13.91, SYBDÖ puan ortalaması 123.69 dur. Öğrencilerin %41.9'unda hafif, %15.5'inde orta ve %7.6'sında şiddetli düzeyde depresyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
2
6
0
2
Order By: Relevance
“…It can be said that individuals with good perception of their health are more careful about exhibiting healthy lifestyle behaviors. Studies in the literature also support this study [14,15].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…It can be said that individuals with good perception of their health are more careful about exhibiting healthy lifestyle behaviors. Studies in the literature also support this study [14,15].…”
Section: Discussionsupporting
confidence: 85%
“…In this study, HLBS scores of students were 78 at the lowest level, 183 at the highest level and the mean score was 124.86 ± 1.092 (Table 1). HLBS scores of students are close to average and similar with the results of studies conducted in other departments of universities [9,14,15]. Higher mean scores were obtained in studies with nursing students [16,17], a study with students in science teaching department [7] and a study with mixed gender group of students [18].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this study, parallel with the findings of Donnelly et al ( 61), Ören and Gençdoğan, (62), Yavuzer and Karataş ( 63) it was determined that gender didn't have a significant effect on depression. On the other hand, İskender et al (64) found that gender significantly differentiates depression scores. According to the findings of this study, it was determined that marital status, educational level, and perceived personality traits significantly differentiated depression symptoms scores.…”
Section: Discussionmentioning
confidence: 97%
“…A review of the national literature revealed no recent study on mental health representing the society as a whole for a considerably long period. Especially since 2000s, studies on depression involving different groups such as women, adolescents, and students who are more sensitive and vulnerable than other groups in the society have been carried out [2,11,12]. However, a large-scale study representing the whole society has not been conducted, and the factors affecting depression have not been examined.…”
mentioning
confidence: 99%